High serum leptin level is associated with peripheral artery disease in adult peritoneal dialysis patients - Yu-Hsien Lai; Chih-Hsien Wang; Jen-Pi Tsai; Jia-Sian Hou; Chung-Jen Lee; Bang-Gee Hsu (Tzu Chi Medical Journal)
Objective: Peripheral artery disease (PAD) is associated with systemic atherosclerosis and indicates an increased risk of mortality in peritoneal dialysis (PD) patients. A high leptin level accelerates atherosclerosis in apoE-deficient mice. The purpose of this study was to examine the association of serum leptin level and PAD in adult PD patients. Materials and Methods: The clinical characteristics of sixty PD patients recruited from June 2015 to October 2016 were obtained. Serum leptin concentrations were determined. Ankle–brachial index (ABI) values were measured and those with a left or right ABI <0.9 were defined as the low ABI group. Results: Twenty of these 60 PD patients (33.3%) had diabetes mellitus and 32 patients (53.3%) had hypertension. Thirteen PD patients (21.7%) were in the low ABI group. Higher serum leptin (P = 0.002) and C-reactive protein (CRP, P < 0.001) levels were found in the low ABI group compared with those in the normal ABI group. More number of patients with diabetes (P = 0.015) and current smokers (P = 0.037) were noted in the low ABI group than in the normal ABI group. After adjustment for factors that were significantly associated with PAD in multivariate logistic regression analysis, each increase of 1 ng/mL in the serum leptin level (odds ratio [OR], 1.062; 95% confidence interval [CI], 1.014–1.114; P = 0.012) and each increase of 0.1 mg/dL in the serum CRP level (OR, 1.107; 95% CI, 1.011–1.211; P = 0.028) were found to be independent predictors of PAD in PD patients. Conclusion: Higher serum leptin and CRP levels correlated positively with the diagnosis of PAD in PD patients.